2017
DOI: 10.21873/anticanres.11584
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Imaging Methods for Chemotherapy-related Cardiotoxicity Screening and Related Radiation Exposure: Current Practice and Trends

Abstract: Abstract. Background: Radiation exposure is a serious concernwith usage of serial multigated acquisition (MUGA) scans (7.8mSv/study)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…These results may be due to increased knowledge of patients and physicians about radiation risks associated with serial radionuclide ventriculography scans. Moreover, the findings of serial radionuclide ventriculography are similar to the findings of echocardiography and cardiac magnetic resonance imaging [53].…”
Section: Nuclear Cardiac Imaging In Cardio-oncologysupporting
confidence: 71%
“…These results may be due to increased knowledge of patients and physicians about radiation risks associated with serial radionuclide ventriculography scans. Moreover, the findings of serial radionuclide ventriculography are similar to the findings of echocardiography and cardiac magnetic resonance imaging [53].…”
Section: Nuclear Cardiac Imaging In Cardio-oncologysupporting
confidence: 71%
“…Multigated acquisition (MUGA) scanning was once a commonly used method for serial evaluation of cardiotoxicity. Despite low inter-and intra-observer variability, such methodology may be rendered obsolete in modern times due to low sensitivity to subtle changes and radiation exposure [27] (Table 1).…”
Section: Volumetric Assessment and Cmrmentioning
confidence: 99%
“…In addition, MUGA is rarely used for follow-up surveillance of LVEF due to ionizing radiation exposure, an inability to provide morphological and functional information, and an inability to assess pericardial and valvular diseases [ 53 ]. A cross-sectional study showed that the usage of MUGA decreased from 30.4% to 16.7% (from 2011 to 2014), and CMR usage increased from 0.9% to 2.9% [ 54 ].…”
Section: Cmr Imaging Biomarkers In the Assessment Of Cardiotoxicitymentioning
confidence: 99%